PENGENALAN CODING WEB DASAR UNTUK MENINGKATKAN LITERASI DIGITAL SISWA KELAS VI SD - Ar Rahman, Muhammad Hafiz; Rifqo, Muhammad Husni; Yuniarti, Rina (Aspirasi Masyarakat, 2025)
Form of digital literacy introduced to elementary school children is computer programming, or coding The development of information and communication technology demands that everyone develop digital literacy skills from an early age. One important. However, elementary school students rarely have the opportunity to learn coding directly in the school environment. This situation is a major problem that prompted the implementation of community service activities at SD Negeri 27 Bengkulu. The objective of the activity was to introduce the basics of web programming to sixth-grade students so they have a basic understanding of how to build simple web pages. The methods used in this activity included brief explanations, demonstrations, and hands-on practice. The material provided included an introduction to HTML structure, the use of CSS to enhance the appearance, and the application of simple JavaScript for interaction. The results of the activity showed that students were able to understand basic coding concepts, although they still encountered obstacles such as coding errors. Through mentoring and practice, students were able to correct these errors and produce simple web pages. In conclusion, introducing coding from an early age can improve students' digital literacy while fostering curiosity and computational thinking, which are useful for facing the challenges of the digital era.